2014
DOI: 10.1111/cdev.12293
|View full text |Cite
|
Sign up to set email alerts
|

Language and Cognitive Predictors of Text Comprehension: Evidence From Multivariate Analysis

Abstract: Using data from children in South Korea (N = 145, M age = 6.08), it was determined how low-level language and cognitive skills (vocabulary, syntactic knowledge, and working memory) and high-level cognitive skills (comprehension monitoring and theory of mind [ToM]) are related to listening comprehension and whether listening comprehension and word reading mediate the relations of language and cognitive skills to reading comprehension. Low-level skills predicted comprehension monitoring and ToM, which in turn pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
200
5
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(254 citation statements)
references
References 103 publications
30
200
5
19
Order By: Relevance
“…Since there was no reliable variation in the growth trajectory of comprehension monitoring, vocabulary nor working memory could be used to predict this growth rate since it was fixed. With regards to the association of vocabulary skill but not working memory with the intercept of comprehension monitoring, we find convergence and also a notable difference with a recent study by Kim (2015) of Grade 1 children in South Korea. In…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Since there was no reliable variation in the growth trajectory of comprehension monitoring, vocabulary nor working memory could be used to predict this growth rate since it was fixed. With regards to the association of vocabulary skill but not working memory with the intercept of comprehension monitoring, we find convergence and also a notable difference with a recent study by Kim (2015) of Grade 1 children in South Korea. In…”
Section: Discussioncontrasting
confidence: 82%
“…First, a number of studies have examined the concurrent relations between children's comprehension monitoring and their reading or listening comprehension when controlling for other key variables, such as vocabulary and working memory (Authors, 2001(Authors, , 2004Kim, 2015Kim, , 2016Strasser & Rio, 2014). Such work shows that children's comprehension monitoring ability is a unique source of variance in reading comprehension in 8 to 10-year-olds (Authors, 2004) and listening comprehension and story book understanding in 6-year-olds (Kim, 2015;Strasser & Rio, 2014), although there is some evidence that the effects are only indirect (Kim, 2016). Second, another set of studies have examined comprehension monitoring among children who have difficulties comprehending what they read.…”
Section: Development Of Comprehension Monitoring Among Beginning Readersmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental studies have shown that in children as young as 6 years old, theory-of-mind ability predicts listening comprehension and that listening comprehension, in turn, influences reading-comprehension proficiency (Kim, 2015). This finding is consistent with other findings that inferences involving story character goals contribute to narrative comprehension by 6-year-old children (Lynch & van den Broek, 2007): Recall of a story could be predicted from the number of goal inferences the children made.…”
Section: Social Cognition and Reading Comprehensionsupporting
confidence: 88%
“…The empirical support for the Simple View in typically developing children is extensive (Catts, Herrera, Nielsen, & Bridges, 2015;Hulme & Snowling, 2014;Language and Reading Research Consortium, 2015;Ripoll Salceda et al, 2014), and the model has also been suggested to be useful as a theoretical framework for reading in deaf children (Chamberlain & Mayberry, 2000;Stone et al, 2015). At the same time, it has been suggested that more detailed specification of the cognitive mechanisms involved in the two components of the Simple View would promote greater understanding of reading development (Hulme & Snowling, 2014;Kirby & Savage, 2008;Stuart, Stainthorp, & Snowling, 2008), and attempts have been made to achieve this (e.g., Byrne et al, 2013;Kim & Phillips, 2014;Kim, 2015aKim, , 2015bTunmer & Chapman, 2012;Vellutino, Tunmer, Jaccard, & Chen, 2007).…”
Section: Learning To Comprehend Texts As a Sign Language Usermentioning
confidence: 99%